Integrating discussions on controversial topics into speaking activities to increase students' particapation in English lesons: an action research at the industrial economics and technology college = Lồng ghép việc thảo luận về các chủ đề gây tranh cãi và - Trần, Thị Phương Nga (University of Languages and International Studies, 2017)
66 p. + CD-ROM